Endocrine complications after solid organ transplantation in childhood and adolescents - Yoon, Ji-Hee; Kim, Dohyung; Hwang, Soojin; Kim, Ja Hye; Choi, Jin-Ho (Frontiers in Endocrinology, 2025)
ObjectiveAcute or chronic metabolic derangement following solid organ transplantation (SOT) often leads to endocrine complications, which have become more common as survival rates post-SOT have improved. This study was performed to investigate long-term endocrine complications after SOT in children and adolescents.MethodsThis study included 259 pediatric patients who underwent SOT, including kidney (n = 43), liver (n = 170), lung (n = 5), heart (n = 37), and multi-organ (n = 4), with a minimum follow-up period of 5 years post-transplant. Clinical and endocrinological data were retrospectively collected, including information on growth, obesity, diabetes, dyslipidemia, thyroid disease, bone health, and pubertal development.ResultsOf 259 patients, 203 (78.4%) developed endocrine complications over a median follow-up period of 10.5 years (range, 5.5–16.8). Short stature was common in kidney (58.1%) and multi-organ recipients (100%), whereas the highest rates of obesity were observed in liver recipients (43.5%). Kidney or liver recipients under 13 years of age showed significant improvements in height-standard deviation scores within 5 years post-SOT. Discontinuation of corticosteroids was associated with a reduced risk of short stature 10 years after liver transplantation. Heart recipients had a high prevalence of post-transplant diabetes mellitus (PTDM, 27%). Other endocrine complications included dyslipidemia (40.2%), hypothyroidism (2.8%), and low bone mineral density (31.3%). Among liver recipients, pretransplant obesity was a significant risk factor for development of post-transplant obesity, PTDM, and dyslipidemia. Additionally, liver transplantation at 0–1 years of age increased the risk of obesity, while transplantation at 6–12 years of age, cyclosporine use, and allograft rejection were associated with an increased risk of dyslipidemia.ConclusionsThis study demonstrates that endocrine and metabolic complications are common in pediatric SOT recipients. Effective surveillance and management of these sequelae are crucial to improve long-term quality of life following SOT.